Modelling and solving a congested facility location problem considering systems' and customers' objectives. (2016) - Seifbarghy, Mehdi; Mansouri, Aida
This paper presents a model for the location of facilities subject to congestion. Motivated by applications to locating servers in communication networks, bank branches, automatic teller machines (ATMs), and police services centres in order to ease the access of customers to service centres and to reduce total costs of both customers and service providers, the given model in this research is proposed for situations, in which immobile service facilities are congested by stochastic demand, which originates from nearby customer locations. We aim to locating an optimal number of single server facilities experiencing M/M/1 queuing policy and assigning a set of demand nodes to them in such a way as to optimise three objective functions: cost, time, and quality. Two heuristics in order to find near optimal solutions are proposed and compared using statistical methods in order to determine the best heuristic based on designing a set of numerical examples.